Ever heard about Egyptian Fractions?

3 2006 = 1 A + 1 B \dfrac 3{2006}=\dfrac1A + \dfrac1B How many unordered pairs of positive integers ( A , B ) (A, B) satisfy the equation above?

2 7 6 4 3 5 8 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chris Galanis
Sep 1, 2015

The solution of the problem is equivalent of finding the unordered pairs of (x, y) that satisfy the following equation: 1 x + 1 y = 3 2006 x + y x y = 3 2006 3 x y x + y = 2006 3 x y = 2006 x + 2006 y 3 x y 2006 x = 2006 3 3 y x ( 3 y 2006 ) = 2006 3 ( 3 y 2006 + 2006 ) x ( 3 y 2006 ) = 2006 3 ( 3 y 2006 ) + 200 6 2 3 ( x 2006 3 ) ( 3 y 2006 ) = 200 6 2 3 ( 3 x 2006 ) ( 3 y 2006 ) = 200 6 2 ( 3 x 2006 ) ( 3 y 2006 ) = 2 2 1 7 2 5 9 2 By just observing the equation we see that 2 17 59 2 ( m o d 3 ) Since x and y are symmetrical in this equation we are looking solutions to the equation 2 a 1 7 b 5 9 c + 2006 0 ( m o d 3 ) , 0 a , b , c 2 2 a 2 b 2 c + 2 0 ( m o d 3 ) 2 a + b + c + 2 0 ( m o d 3 ) Thus: ( a + b + c ) = { 0 , 2 , 4 , 6 } But since we are looking for unordered pairs, we can limit ourselves such that: ( a + b + c ) = { 0 , 2 } For (a + b + c) = 0 we get only 1 solution where ( a , b , c ) = ( 0 , 0 , 0 ) For (a + b + c) = 2 we get 6 solutions where ( a , b , c ) = ( 1 , 1 , 0 ) , ( 1 , 0 , 1 ) , ( 0 , 1 , 1 ) , ( 2 , 0 , 0 ) , ( 0 , 2 , 0 ) , ( 0 , 0 , 2 ) Hence there are in total 7 solutions. \text{The solution of the problem is equivalent of finding the unordered pairs} \\ \text{of (x, y) that satisfy the following equation: } \large{\frac1x + \frac1y = \frac{3}{2006}} \\ \Rightarrow \large{\frac{x + y}{xy} = \frac{3}{2006}} \\ \Rightarrow \large{\frac{3xy}{x+y} = 2006} \\ \Rightarrow \large{3xy = 2006x + 2006y} \\ \Rightarrow \large{3xy - 2006x = \frac{2006}{3}\cdot 3y} \\ \Rightarrow \large{x\cdot (3y - 2006) = \frac{2006}{3}\cdot (3y - 2006 + 2006)} \\ \Rightarrow \large{x\cdot (3y - 2006) = \frac{2006}{3}\cdot (3y - 2006) + \frac{2006^2}{3}} \\ \Rightarrow \large{(x - \frac{2006}{3})\cdot (3y - 2006) = \frac{2006^2}{3}} \\ \Rightarrow {(3x - 2006)\cdot(3y - 2006) = 2006^2} \\ \Rightarrow {(3x - 2006)\cdot(3y - 2006) = 2^2\cdot 17^2 \cdot 59^2} \\ \text{By just observing the equation we see that } 2 \equiv 17 \equiv 59 \equiv 2 \pmod {3} \\ \text{Since x and y are symmetrical in this equation we are looking solutions} \\ \text{to the equation } 2^a \cdot 17^b \cdot 59^c + 2006 \equiv 0 \pmod 3 , 0 \leq a, b, c \leq 2 \\ \Rightarrow 2^a \cdot 2^b \cdot 2^c + 2 \equiv 0 \pmod {3} \\ \Rightarrow 2^{a+b+c} + 2 \equiv 0 \pmod {3} \text{ Thus:} (a + b + c) = \Big\{0, 2, 4, 6\Big\} \\ \text{But since we are looking for unordered pairs, we can limit ourselves} \\ \text{such that: } (a + b + c) = \Big\{0, 2\Big\} \\ - \text{For (a + b + c) = 0 we get only 1 solution where } (a, b, c) = (0, 0, 0) \\ - \text{For (a + b + c) = 2 we get 6 solutions where } \\ (a, b, c) = (1, 1, 0), (1, 0, 1), (0, 1, 1), (2, 0, 0), (0, 2, 0), (0, 0, 2) \\ \text{Hence there are in total 7 solutions.}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...